Performance evaluation of electrical discharge machine on titanium alloy using copper impregnated graphite electrode - Mohd. Isa @ Hamid, Mohd. Halimudin (2010)
Electrical discharge machining (EDM) which is very prominent amongst the non conventional machining methods is expected to be used quite extensively in machining titanium alloys due to the favorable features and advantages that it offers. This thesis presents the EDMing of titanium alloy (Ti-6246) using copper impregnanted graphite electrode with diameter of 8 mm. The main purpose of this study was to investigate the influenced of various parameters involved in EDM on the machining characteristics, namely, material removal rate (MRR), electrode wear ratio (EWR), surface roughness (Ra) and overcut. In this investigation, the machining trials were performed using a Sodick linear motor EDM sinker series AM3L The experimental plan for the processes were conducted according to the design of experimental (DOE) and the results were statistically evaluated using analysis of variance (ANOVA). Results showed that current was the most significant parameter that influenced the machining responses on EDM of Ti-6246. Confirmation tests were also conducted for the selected conditions for each machining characteristics in order to verify and compare the results from the theoretical prediction using Design Expert software and experimental confirmation tests. Overall, the results from the confirmation tests showed that the percentage of performance was acceptable due to all results obtained were within the allowable values which was less than 15% of marginal error.